Inequitable gender norms and its associated factors among university students in southern Ethiopia: a cross-sectional study, 2022 - Kelecha, Yirgalem Tola; Ayele, Amanuel Albene; Goda, Habtamu Samuel; Demissie, Mesarch Hailu; Toma, Temesgen Mohammed (Frontiers in Public Health, 2024)
BackgroundGender defined as the socially constructed roles, behaviors, activities, and characteristics that society deems appropriate for men, women, and other gender identities. Inequitable gender norms promote male dominance and aggressiveness while portraying women as being subservient. Ensuring equitable gender norms is a prerequisite for achieving gender equality in a society. The rise in maternal mortality and morbidity, adolescent pregnancies, unwanted pregnancies, unsafe abortions, HIV/AIDS, gender-based violence, and obstacles to reproductive health care are all linked to inequitable gender norms. On the other hand, not much is known regarding inequitable gender norms and their correlation in our setting.ObjectiveThe purpose of this study was to evaluate university students’ attitudes regarding inequitable gender norms and responsible factors.DesignBetween October 25 and November 10, 2022, students from Jinka and Arba Minch University participated in an institution-based cross-sectional study.MethodsA total of 635 students were selected using a multi-stage sampling technique. The Gender Equitable Men Scale was employed to evaluate inequitable gender norms. Data were verified and entered into Epi-Data Version 3.1, then analyzed using SPSS Version 25.0. Binary logistic regression was initially used to identify potential factors associated with inequitable gender norms, variables having a p-value <0.25 in bivariate analysis considered for multivariable regression. The final model’s fit was assessed using the Hosmer–Lemeshow goodness-of-fit statistic, confirming its adequacy. Statistical significance was determined at a threshold of p < 0.05.ResultsOf the study participants, 44.1% (95% CI: 40.10, 48.10%) had an inequitable gender norm, while the mean score for a inequitable gender norm was 61.4 (SD 8.4). Inequitable gender norm was associated with sex being male (AOR = 1.75, 95%CI: 1.19, 2.56), romantic relationship breakup (AOR = 2.10, 95% CI: 1.14, 3.99), and having a negative attitude toward gender equality (AOR = 3,14, 95% CI: 2.15, 4.58).ConclusionA notable number of participants expressed support for inequitable gender norms. This underscores the importance of comprehensive efforts by relevant stakeholders to address identified factors and promote equitable gender norms among university students.